2016
DOI: 10.5194/acp-16-12897-2016
|View full text |Cite
|
Sign up to set email alerts
|

Current understanding of the driving mechanisms for spatiotemporal variations of atmospheric speciated mercury: a review

Abstract: Abstract. Atmospheric mercury (Hg) is a global pollutant and thought to be the main source of mercury in oceanic and remote terrestrial systems, where it becomes methylated and bioavailable; hence, atmospheric mercury pollution has global consequences for both human and ecosystem health. Understanding of spatial and temporal variations of atmospheric speciated mercury can advance our knowledge of mercury cycling in various environments. This review summarized spatiotemporal variations of total gaseous mercury … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
69
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 183 publications
(672 reference statements)
7
69
1
Order By: Relevance
“…The median concentration of TGM/GEM in global continental remote areas was 1.6 ng m −3 (180 ppqv), estimated from a large body of measurement studies (Mao et al, 2016), and the background concentration of GEM in the Northern Hemisphere was 1.5-1.7 ng m −3 (168-190 ppqv) (Lindberg et al, 2007). Urban concentrations of GEM/TGM in the US varied between 0.05 and 324 ng m −3 (5.6-36 288 ppqv) (Mao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The median concentration of TGM/GEM in global continental remote areas was 1.6 ng m −3 (180 ppqv), estimated from a large body of measurement studies (Mao et al, 2016), and the background concentration of GEM in the Northern Hemisphere was 1.5-1.7 ng m −3 (168-190 ppqv) (Lindberg et al, 2007). Urban concentrations of GEM/TGM in the US varied between 0.05 and 324 ng m −3 (5.6-36 288 ppqv) (Mao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Urban concentrations of GEM/TGM in the US varied between 0.05 and 324 ng m −3 (5.6-36 288 ppqv) (Mao et al, 2016). In comparison, urban concentrations and their temporal variability were larger than rural, remote, and high-elevation concentrations in the Northern Hemisphere (e.g., Kim and Kim, 2001;Feng et al, 2003;Denis et al, 2006;Liu et al, 2007;Peterson et al, 2009;Sprovieri et al, 2010;Zhu et al, 2012;Lan et al, 2012Lan et al, , 2014Chen et al, 2013;Civerolo et al, 2014;Fu et al, 2015;Brown et al, 2015;Mao et al, 2016, and references therein) owing to numerous controlling factors, including anthropogenic and legacy emissions, deposition, meteorology, transport, and atmospheric chemistry (Mao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atmosphere Hg speciation is operationally defined as gaseous elemental mercury (GEM), gaseous oxidized mercury (GOM), and particulate bound mercury (PBM). GEM is relatively inert comprising about 75% of the global atmospheric Hg pool (Gustin et al, ) with lifetime of 0.5–1 year and is considered as the main form of Hg transported over long distances (Driscoll et al, ; Mao et al, ). With relatively short atmospheric lifetimes ranging from hours to weeks, GOM and PBM can be emitted directly or produced from oxidation of GEM (Cole et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Mercury transformation mechanisms and speciation profiles for Hg formed in and released from flue gases of coal-fired boilers, non-ferrous metal smelters, cement plants, iron and steel plants, waste incinerators and biomass burning were documented in Zhang et al (2016a). Worldwide measurements of Hg spanning the past 4 decades were reviewed in Mao et al (2016) together with the mecha-nisms driving the observed spatiotemporal variations of speciated Hg in various environments including oceans, continents, high elevation, the free troposphere, and low to high latitudes. Current knowledge of Hg dry deposition was reviewed in Wright et al (2016), including dry deposition algorithms used in chemical transport models and at monitoring sites, measurement methods and quantification of dry deposition of oxidized Hg, and Hg in litterfall and throughfall.…”
Section: Introductionmentioning
confidence: 99%